Far from the madding crowd - Hardy, Thomas, 1840-1928; Falck-Yi, Suzanne B.; Gatrell, Simon (Oxford ; New York : Oxford University Press, 1991)
Far from the Madding Crowd was the first of Hardy's novels to apply the name of Wessex to the landscape of south-west England, and the first to gain him widespread popularity as a novelist. When the beautiful and spirited Bathsheba Everdene inherits her own farm, she attracts three very different suitors; the seemingly commonplace man-of-the-soil Gabriel Oak, the dashing young soldier Francis Troy, and the respectable, middle-aged Farmer Boldwood. Her choice, and the tragedy it provokes, lie at the centre of Hardy's ambivalent story. This edition presents a new text of the novel restoring several manuscript passages never before published with the novel and many of the 1901 revisions missing from nearly all modern versions
Includes bibliographical references (p. [xxxvii]-xxxix)
Keywords: Women farmers -- Fiction; Triangles (Interpersonal relations) -- Fiction; Farm life -- Fiction; Farm life -- Fiction; Wessex (England) -- Fiction; English fiction; Didactic fiction; Pastoral fiction; Romance fiction; Novels